Estudio de la función cuadrática, que involucran parámetros, con el apoyo del GeoGebra - Saravia Molina, Nancy Edith (2021)
In this workshop we will share a proposal for teaching quadratic functions whose correspondence rules contain parameters in their mathematical expression and certain conditions that their range must fulfill. We will use GeoGebra as a support tool for the validation of the parameter values obtained in the algebraic process. This workshop has two purposes, the first is to propose problems with context in which the solutions involve real numbers, and the second is to present to teachers the potential of GeoGebra to validate algebraic processes. Likewise, we are interested in generating a space to discuss the advantages and disadvantages offered by GeoGebra tools in the verification of results obtained algebraically and to reflect on its incorporation in our classes. As for the didactic analysis, aspects of the Theory of Semiotic Representation Registers are taken. In relation to the methodology, it is qualitative. Finally, the need to use different representations is evidenced and the pertinence of the use of GeoGebra, which favors learning and teaching.